Factors predicting ablation site recurrence following percutaneous microwave ablation of colorectal hepatic metastases. Issue 9 (September 2019) - Urbonas, Tomas; Anderson, Ewan M.; Gordon-Weeks, Alex N.; Kabir, Syed I.; Soonawalla, Zahir; Silva, Michael A.; Gleeson, Fergus V.; Reddy, Srikanth
Abstract: Background: Microwave ablation (MWA) is a recognised treatment option for liver metastases. The size of the tumour is a well-established factor that influences the success of MWA. However, the effect of "heat sink" on the success of MWA for hepatic metastases is unclear. The aim of this study was to determine whether heat sink effect is a factor that contributes to ablation site recurrence (ASR). Methods: A prospectively maintained database of patients who underwent percutaneous MWA for treatment of colorectal liver metastases was analysed. Imaging and demographic characteristics were compared between metastases that recurred following ablation and those that did not. Proximity to a large hepatic vein was defined as <10 mm. Results: 126 ablations in 87 patients met the inclusion criteria and were studied over a median follow-up period of 28 (12–75) months. ASR was detected in 43 ablations (34%) and was associated with clinical risk score (CRS) ≥2 (OR 2.2 95% CI 1.3–3.3, p = 0.029), metastasis size (OR 0.953 95% CI (0.929–0.978), p < 0.001) and proximity to a large hepatic vein (OR 7.5 95%CI 2.4–22.8, p < 0.001). Proximity to a large hepatic vein was not associated with reduced overall survival (OS) but was associated with liver-specific recurrence (HR 4.7 95%CI 1.7–12.5, p = 0.004). Conclusions: In addition to tumour size proximity to large hepatic venous structures is an independent predictor of ASR and liver-specific recurrence following MWA. However, this was not associated with overall survival.